Application of Brand Ambassador and Product Reviews to Improve Purchasing Decisions for Scarlett Whitening Products - Situmorang, Irvan Rolyesh (Outline Journal of Management and Accounting, 2024)
The purpose of this research is to determine the influence of brand ambassadors and product reviews on purchase decisions for Scarlett Whitening Products, both partially and simultaneously. This research uses a quantitative methodology with a Likert scale for measurement. The population in this study cannot be known, so the sample collection uses the "Hair" formula, which means the number of indicators is multiplied by the maximum criterion, namely 10. The regression used is multiple linear regression. The results of the first hypothesis show that brand ambassadors have no influence on purchasing decisions for Scalett Whitening products. The results of the second hypothesis show that product reviews have a positive and significant effect on purchasing decisions for Scallett Whitening Products. The results of the third hypothesis show that brand ambassadors and product reviews have a positive and significant effect on purchasing decisions for Scalett Whitening Products at Plaza Medan Fair. The results of the coefficient of determination show that brand ambassadors and product reviews contributed 93.8%, while the remaining 6.2% was influenced by other variables not examined in this research